Prospects for the Use of New Technologies to Combat Multidrug-Resistant Bacteria - Lima, Renata; Del Fiol, Fernando Sá; Balcão, Victor M. (Frontiers in Pharmacology, 2019)
The increasing use of antibiotics is being driven by factors such as the aging of the population, increased occurrence of infections, and greater prevalence of chronic diseases that require antimicrobial treatment. The excessive and unnecessary use of antibiotics in humans has led to the emergence of bacteria resistant to the antibiotics currently available, as well as to the selective development of other microorganisms, hence contributing to the widespread dissemination of resistance genes at the environmental level. Due to this, attempts are being made to develop new techniques to combat resistant bacteria, among them the use of strictly lytic bacteriophage particles, CRISPR-Cas, and nanotechnology. The use of these technologies, alone or in combination, is promising for solving a problem that humanity faces today and that could lead to human extinction: the domination of pathogenic bacteria resistant to artificial drugs. This prospective paper discusses the potential of bacteriophage particles, CRISPR-Cas, and nanotechnology for use in combating human (bacterial) infections.